Distance decay in activity chains analysis. A Belgian case study - Isabelle Thomas; Ann Verhetsel; Hakim Hammadou; Dries Vanhofstraeten (European Regional Science Association (ERSA), 2003)
This paper aims at measuring and testing the distance decay effect in activity chains. It enables one to show how far distance constrains the length of the trips and if there are borders effects. Two Belgian data bases are used: one conducted at the national level, the other at a regional level. Statistical tests are conducted for (1) several definitions of the trip and chain, (2) several distance measurements (time or kilometers), (3) several purposes of trips, and (4) different categories of travellers. This exploratory data analysis enables one to gain information about the spatial aspects of the activity chains and to get a better fit in the gravity type models.
Keywords: 330